Fluorine-doped Fe-N-C composite material as well as preparation method, application and regeneration thereof

By introducing fluorine atoms into the Fe-N-C composite material to form a fluorine-doped Fe-N-C composite material, the problem of decreased activity and insufficient stability of Fe-based materials in water pollution treatment is solved, significantly improved reaction activity and stability is achieved, and an environmentally friendly regeneration strategy is provided.

CN119707074AActive Publication Date: 2025-03-28NANJING UNIV

Patent Information

Application Number
CN202411996664.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-28
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

Fe-based materials have problems in water pollution treatment with reduced reduction activity, insufficient stability and secondary pollution of water bodies caused by Fe ion leaching.

Method used

By mixing the iron precursor, zinc salt, organic ligand and organic solvent, Fe@ZIF-8 material was synthesized and carbonized twice to obtain a fluorine-doped Fe-N-C composite material. This material enhances the reactive activity by introducing fluorine atoms, inhibits Fe leaching and improves stability.

Benefits of technology

The activity of the Fe-N-C composite after fluorine doping was increased by 2.35 times, and its stability was greatly increased. It could maintain a 91-100% reduction and removal effect of bromate ion under pH 4.0-10, and maintain a 100% removal effect during 5 fluorine doping carbonization and regeneration-reuse cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707074A_ABST
    Figure CN119707074A_ABST
Patent Text Reader

Abstract

The invention provides a fluorine-doped Fe-N-C composite material as well as a preparation method, application and regeneration thereof, and belongs to the technical field of water pollution. The preparation method comprises the following steps: firstly, mixing an iron precursor, zinc salt, an organic ligand and an organic solvent to synthesize a Fe-doped metal organic framework Fe (at) ZIF-8 material, and then carbonizing the Fe-doped metal organic framework Fe (at) ZIF-8 material into a Fe-N-C material; and then Fe-N-C and a fluorine source are mixed and subjected to secondary carbonization, and the fluorine-doped Fe-N-C composite material is obtained. Fluorine atoms are introduced into the Fe-N-C material and generate axial coordination with Fe in the center of FeN4, the fluorine element with high electronegativity can effectively improve the isoelectric point of the Fe-N-C material, the reaction activity of the material is enhanced, Fe leaching of the material in the reaction process is inhibited, and the stability of the material is improved. In addition, the prepared fluorine-doped Fe-N-C composite material can continue to be recycled through fluorine doping regeneration, and high reduction activity and stability are kept.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water pollution, and in particular to a fluorine-doped Fe-NC composite material and a preparation method, application and regeneration thereof. Background Art

[0002] Fe-based materials have shown significant advantages in the field of water pollution and environmental remediation, but their application still has some limitations and disadvantages. Specifically, materials with low-valent Fe active species (such as zero-valent iron, Fe 2+ ions, etc.) are easily affected by oxidation during storage and actual application. The iron oxide layer formed will shield the active sites, resulting in a decrease in reduction activity. The performance of Fe-based materials is highly dependent on the environmental pH value. In an acidic environment, the material exhibits a strong reduction ability. However, under neutral or alkaline conditions, its reduction efficiency will drop significantly. This feature greatly limits the application range of the material. In addition, during the use of Fe-based materials with high reactivity, Fe ion leaching is often inevitable, resulting in the loss of active components and secondary pollution of water bodies. Another issue worth noting is that Fe-based materials, as chemical reducing agents, are often inactivated after use due to surface oxidation and agglomeration of active component particles.

[0003] In recent years, researchers have adopted many strategies to improve the reduction performance of Fe-based reducing materials. For example, the metal-support interaction produced by embedding or loading Fe species on a carrier can improve the dispersibility of the metal and increase its surface free energy. Carbon-based materials are a common carrier with chemical and mechanical stability, and the structure and surface properties of carbon materials are easy to control. Among them, doping Fe-carbon composites with heteroatoms (N, P, B, S, etc.) can change the electronic structure of the carbon matrix and improve the conductivity of the material. The doping of heteroatoms can form a series of functional groups on the surface of the material, thereby changing the surface acid-base properties, hydrophilicity, adsorption sites and active sites of the material. Therefore, doping and modifying Fe-C materials to enhance their reactivity and stability, as well as exploring effective methods to regenerate and recycle inactivated Fe-based reducing agents, are particularly critical for improving the sustainability and practicality of Fe-based materials. Summary of the invention

[0004] The object of the present invention is to provide a fluorine-doped Fe-NC composite material and a preparation method, application and regeneration thereof, which can improve the reduction activity and stability of Fe-based materials.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a fluorine-doped Fe-NC composite material, comprising the following steps:

[0007] The iron precursor, zinc salt, organic ligand and organic solvent are mixed and polymerized to obtain Fe@ZIF-8;

[0008] Carrying out a first carbonization of the Fe@ZIF-8 to obtain a Fe-NC material;

[0009] The Fe-NC material is mixed with a fluorine source solution and subjected to a second carbonization to obtain a fluorine-doped Fe-NC composite material.

[0010] Preferably, the iron precursor includes one or more of ferric acetylacetonate, ferrous acetylacetonate, ferrocene and ferrophthalocyanine; the zinc salt includes one or more of zinc nitrate, zinc chloride and zinc sulfate; the organic ligand includes 2-methylimidazole; and the organic solvent includes methanol.

[0011] Preferably, the molar ratio of the iron element in the iron precursor, the zinc element in the zinc salt and the organic ligand is 0.01-1.5:1:2-16.

[0012] Preferably, the polymerization reaction temperature is 20 to 160° C. and the time is 4 to 36 hours.

[0013] Preferably, the temperature of the first carbonization is 850-1050° C., and the time is 1-4 hours.

[0014] Preferably, the fluorine source in the fluorine source solution includes one or more of perfluorooctanoic acid, perfluorononanoic acid, perfluorodecanoic acid and perfluoroundecanoic acid; the concentration of the fluorine source solution is 5 to 100 mg / L; and the concentration of the Fe-NC material in the fluorine source solution is 0.2 to 2 g / L.

[0015] Preferably, the temperature of the second carbonization is 600-800° C., and the time is 1-4 hours.

[0016] The present invention provides a fluorine-doped Fe-NC composite material prepared by the preparation method described in the above technical solution.

[0017] The present invention provides the use of the fluorine-doped Fe-NC composite material described in the above technical solution in reducing oxygen-containing salt pollutants in water.

[0018] The present invention provides a method for regenerating the fluorine-doped Fe-NC composite material described in the above technical solution, comprising the following steps:

[0019] The fluorine-doped Fe-NC composite material after the pollutant reduction treatment in water is mixed with a fluorine compound to carry out a fluorination regeneration reaction.

[0020] The present invention provides a method for preparing a fluorine-doped Fe-NC composite material, wherein an iron precursor, a zinc salt, an organic ligand and an organic solvent are first mixed to synthesize an Fe-doped metal organic framework Fe@ZIF-8 material, which is then carbonized into a Fe-NC material; a Fe-NC material having a strong adsorption capacity for anions is used as a precursor, and then the Fe-NC is mixed with a fluorine source and subjected to secondary carbonization to obtain a fluorine-doped Fe-NC composite material. The present invention introduces fluorine atoms into the Fe-NC material to produce axial coordination with the Fe at the center of FeN4. The fluorine element with high electronegativity can effectively increase the isoelectric point of the Fe-NC material, enhance the reaction activity of the material, and inhibit the Fe leaching of the material during the reaction process, thereby improving the stability of the material. The results of the embodiment show that after fluorine doping, the activity of the material is increased by 2.35 times, and the stability is greatly increased. Under the condition of pH=4.0~10, the material can achieve a bromate ion reduction removal effect of 91~100%, and no Fe leaching phenomenon is detected during the reaction process.

[0021] The fluorine-doped Fe-NC composite material prepared by the present invention can be further reused through fluorine doping regeneration and maintain high reduction activity and stability. During the regeneration process, perfluorocarboxylic acid can act as a self-sacrificial carbon source and participate in the carbon thermal reduction of the deactivated Fe-NC material. Through 5 consecutive fluorine-doped carbonization regeneration-reuse cycle experiments, the material can still maintain a 100% removal effect on bromate. The present invention demonstrates the effectiveness of improving the performance of Fe-NC materials through fluorine doping technology and provides an environmentally friendly strategy for regenerating Fe-based materials.

[0022] Furthermore, the present invention utilizes the persistent pollutant perfluorocarboxylic acid as a fluorine source to fluorine-dope the Fe-NC material. Perfluorocarboxylic acids (PFCAs) belong to the perfluoroalkyl substance (PFAS) family, and are a class of compounds composed of a perfluorocarbon chain and a carboxylic acid group. The carboxylic acid group in the molecular structure of perfluorocarboxylic acids gives them certain water-solubility properties, and they can be adsorbed by materials with positive charges on the surface. The present invention innovatively utilizes perfluorocarboxylic acids as a fluorine doping source to prepare fluorine-doped Fe-NC composite materials, providing a promising solution for the resource recycling of perfluoro pollutants and alleviating their environmental pollution problems. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 XRD spectra of Fe(0.125)@NC and Fe(0.125)@FNC in Example 1, Fe(0.125)@FNC' after reaction in Application Example 3, and fluorine-doped regenerated material Fe(0.125)@FNC-1;

[0024] Figure 2(a) is a TEM image of Fe(0.125)@FNC prepared in Example 1; (b-e) are element mapping images of Fe(0.125)@FNC: (b) is C element, (c) is F element, (d) is N element, and (e) is Fe element;

[0025] Figure 3 XPS spectra of the N1s region of different materials prepared in Example 1: (a) is Fe(0.125)@NC, (b) is Fe(0.125)@FNC;

[0026] Figure 4 XPS spectra of the C1s region of different materials prepared in Example 1: (a) is Fe(0.125)@NC, (b) is Fe(0.125)@FNC;

[0027] Figure 5 (a) shows the effect of different materials on BrO3 - The reduction rate changes with reaction time, (b) the reaction activity of different materials;

[0028] Figure 6 The effects of different initial pH values ​​on the reduction reaction of different materials prepared in Example 1, (a) is Fe(0.125)@NC, (b) is Fe(0.125)@FNC;

[0029] Figure 7 This is a diagram showing the fluorine-doped regeneration and reuse effect of the Fe(0.125)@FNC material prepared in Example 1. DETAILED DESCRIPTION

[0030] In the present invention, unless otherwise specified, the required raw materials or reagents are commercially available products well known to those skilled in the art.

[0031] The present invention provides a method for preparing a fluorine-doped Fe-NC composite material, comprising the following steps:

[0032] The iron precursor, zinc salt, organic ligand and organic solvent are mixed and polymerized to obtain Fe@ZIF-8;

[0033] Carrying out a first carbonization of the Fe@ZIF-8 to obtain a Fe-NC material;

[0034] The Fe-NC material is mixed with a fluorine source solution and subjected to a second carbonization to obtain a fluorine-doped Fe-NC composite material.

[0035] In the present invention, the iron precursor preferably includes one or more of ferric acetylacetonate, ferrous acetylacetonate, ferrocene and ferrophthalocyanine; the zinc salt preferably includes one or more of zinc nitrate, zinc chloride and zinc sulfate; the organic ligand preferably includes 2-methylimidazole; the organic solvent preferably includes methanol. When the iron precursor or zinc salt is two or more of the above, the present invention has no special restrictions on the ratio of different types of iron precursors or zinc salts, and any ratio is acceptable.

[0036] In the present invention, the molar ratio of the iron element in the iron precursor, the zinc element in the zinc salt and the organic ligand is preferably 0.01-1.5:1:2-16, and more preferably 0.0625-0.25:1:8.

[0037] The present invention preferably mixes an organic ligand with a first portion of an organic solvent to obtain a first mixed solution, and mixes an iron precursor and a zinc salt with a second portion of an organic solvent to obtain a second mixed solution (wherein the total amount of the first portion of an organic solvent and the second portion of an organic solvent is the total amount of organic solvent added); the first mixed solution and the second mixed solution are then mixed, stirred, and then subjected to polymerization reaction under static conditions; the stirring time is preferably 5 to 120 min, more preferably 60 min, and the stirring rate is preferably 200 to 800 rpm, more preferably 600 rpm; the ratio of the number of moles of iron element in the iron precursor to the volume of the second portion of an organic solvent is preferably 0.01 to 1.5 mmol:15 to 30 mL, more preferably 0.125 to 0.25:20 mL.

[0038] In the present invention, the polymerization reaction temperature is preferably 20 to 160° C., more preferably 80 to 120° C., and the time is preferably 4 to 36 hours, more preferably 12 to 24 hours. During the polymerization process, the ZIF-8 framework separates and encapsulates the iron precursor molecules.

[0039] After the polymerization reaction is completed, the obtained mixture is repeatedly centrifuged and washed with methanol, and then vacuum dried to obtain the Fe@ZIF-8 material.

[0040] In the present invention, the first carbonization is preferably carried out under a protective atmosphere, and the protective atmosphere is preferably high-purity nitrogen or high-purity argon; the protective gas flow rate is preferably 25 to 150 mL min -1 .

[0041] In the present invention, the temperature of the first carbonization is preferably 850-1050°C, more preferably 900-950°C; the time is preferably 1-4h, more preferably 2h; the present invention has no special limitation on the heating rate of heating to the temperature of the first carbonization, and the heating rate can be carried out according to the heating rate well known in the art. During the first carbonization process, the Fe@ZIF-8 material is pyrolyzed and carbonized to become the Fe-NC material.

[0042] In the present invention, the loading amount of Fe in the Fe-NC material is preferably 0.15-21.1 wt %, preferably 0.96-4.21 wt %, and more preferably 1.97 wt %.

[0043] In the present invention, the fluorine source in the fluorine source solution preferably includes one or more of perfluorooctanoic acid, perfluorononanoic acid, perfluorodecanoic acid and perfluoroundecanoic acid; when the fluorine source is two or more of the above, the present invention has no special limitation on the ratio of different types of fluorine sources, and any ratio is acceptable.

[0044] In the present invention, the fluorine source solution is preferably an aqueous solution of a fluorine source; the concentration of the fluorine source solution is preferably 5 to 100 mg / L; the concentration of the Fe-NC material in the fluorine source solution is preferably 0.2 to 2 g / L, more preferably 1.0 to 1.5 g / L, and further preferably 1 g / L.

[0045] In the present invention, the mixing method of the Fe-NC material and the fluorine source is preferably: placing the Fe-NC material in a fluorine source solution for a mixing time of 6 to 24 hours, more preferably 16 hours, filtering and separating, and vacuum drying at a temperature of 60 to 100°C (more preferably 80°C) before performing a second carbonization.

[0046] In the present invention, the second carbonization is preferably carried out under a protective atmosphere, and the protective atmosphere is preferably high-purity nitrogen or high-purity argon; the protective gas flow rate is preferably 25 to 150 mL min -1 .

[0047] In the present invention, the temperature of the second carbonization is preferably 600-800° C., more preferably 650-700° C., and the time is preferably 1-4 hours, more preferably 2-3 hours. During the second carbonization, the fluorine source in the mixture performs fluorine doping on the Fe-NC material.

[0048] In the present invention, the loading amount of Fe in the fluorine-doped Fe-NC composite material is preferably 0.97 to 4.35 wt %, and more preferably 1.99 to 3.5 wt %.

[0049] The present invention provides a fluorine-doped Fe-NC composite material prepared by the preparation method described in the above technical solution.

[0050] The present invention provides the use of the fluorine-doped Fe-NC composite material described in the above technical solution in reducing oxygen-containing salt pollutants in water.

[0051] The present invention has no special limitation on the specific types of the oxygen-containing salt pollutants, and the corresponding oxygen-containing salt pollutants well known in the art can be used. In the embodiments of the present invention, a bromate ion aqueous solution is specifically used as a simulated oxygen-containing salt wastewater.

[0052] In the present invention, the application method is preferably to mix the fluorine-doped Fe-NC composite material with oxygen-containing salt wastewater for reduction.

[0053] In the present invention, the reduction reaction is preferably carried out under normal temperature and pressure conditions, and the pH of the reduction reaction is 4.0-10.0, preferably 6.0; the concentration of the fluorine-doped Fe-NC composite material in the oxygen-containing salt wastewater is preferably 0.15-0.30 g / L, more preferably 0.25 g / L; the initial concentration of the oxygen-containing salt in the oxygen-containing salt wastewater is preferably 0.04-0.10 mmol / L, more preferably 0.08 mmol / L; the reduction reaction time is preferably 1-4 h, more preferably 2 h; the stirring rate is preferably 200-2000 rpm, more preferably 400-1000 rpm.

[0054] The present invention has no particular limitation on the application method, and the application can be carried out according to methods well known in the art.

[0055] The present invention provides a method for regenerating the fluorine-doped Fe-NC composite material described in the above technical solution, comprising the following steps:

[0056] The fluorine-doped Fe-NC composite material after the pollutant reduction treatment in water is mixed with a fluorine compound to carry out a fluorination regeneration reaction.

[0057] The conditions of the fluorination regeneration reaction of the present invention are the same as those of the second carbonization; the type of the fluorine compound is the same as the fluorine source described above.

[0058] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0059] Example 1

[0060] (1) Preparation of metal organic framework ZIF-8 material of confined iron precursor molecules (Fe(x)@ZIF-8):

[0061] 16 mmol of 2-methylimidazole was dissolved in 20 mL of methanol solution and mixed evenly to obtain solution A; 2 mmol of zinc nitrate hexahydrate and 0.25 mmol of ferric acetylacetonate (Fe(acac)3) were dissolved in 20 mL of methanol solution and mixed evenly to obtain solution B; solution A was added to solution B, stirred at 600 rpm for 1 hour, and then allowed to stand in a reactor for polymerization for 4 hours at a polymerization temperature of 120°C. The obtained mixture was repeatedly centrifuged and washed with methanol, and dried in a vacuum oven at 120°C to obtain Fe(x)@ZIF-8 material, wherein x is the molar ratio of Fe and Zn elements, that is, Fe(0.125)@ZIF-8 material was obtained;

[0062] (2) Preparation of Fe-NC materials (Fe(0.125)@NC) and fluorine-doped Fe-NC composites (Fe(0.125)@FNC) by carbonization:

[0063] The Fe(0.125)@ZIF-8 was placed in the middle of the constant temperature zone of the tube furnace and heated at 25 mL min -1 In an atmosphere of high-purity nitrogen (purity ≥ 99.999%), the temperature was raised at a rate of 5°C min -1 The tube furnace was heated to 950°C and maintained for 2 h for carbonization treatment to obtain Fe(0.125)@NC material, wherein the Fe loading was 1.97 wt%;

[0064] Fe(0.125)@NC was mixed with 1000 mL of 100 mg / L perfluorooctanoic acid aqueous solution to make the mass concentration of Fe(0.125)@NC in the perfluorooctanoic acid solution 1.0 g / L. The mixing time was 16 h. The material was filtered and separated. After drying in a vacuum oven at 80 °C, it was placed in the middle of the constant temperature zone of a tube furnace and heated at 25 mL min -1 In an atmosphere of high-purity nitrogen (purity ≥ 99.999%), the temperature was raised at a rate of 5°C min -1 The temperature of the tube furnace was raised to 700°C and maintained for 2 hours to perform fluorine doping carbonization treatment to obtain the material Fe(0.125)@FNC; the Fe loading was 1.99wt%.

[0065] Example 2

[0066] The only difference from Example 1 is that the amount of iron acetylacetonate (Fe(acac)3) used is 0.125 mmol, and the material Fe(0.0625)@NC is obtained; wherein the Fe loading is 0.96 wt%;

[0067] Finally, the material Fe(0.0625)@FNC was prepared, in which the Fe loading was 0.97wt%.

[0068] Example 3

[0069] The only difference from Example 1 is that the amount of iron acetylacetonate (Fe(acac)3) used is 0.5 mmol, and the material Fe(0.25)@NC is obtained; wherein the Fe loading is 4.21 wt%;

[0070] Finally, the material Fe(0.25)@FNC was prepared, in which the Fe loading was 4.35wt%.

[0071] Test Example 1

[0072] 1) The X-ray diffraction (XRD) results of the Fe-NC material (Fe(0.125)@NC) and the fluorine-doped Fe-NC composite material (Fe(0.125)@FNC) prepared in Example 1 are as follows: Figure 1 As shown in the figure, the material only has two broad diffraction peaks at 24.3 and 43.7°, which are respectively attributed to the (0,0,2) and (1,0,1) crystal planes of graphite carbon. The intensity and position of the peaks do not change due to the deactivation or regeneration carbonization process of the material, indicating that the Fe active component in the material is still in a highly dispersed state.

[0073] 2) The fluorine-doped Fe-NC composite material (Fe(0.125)@FNC) prepared in Example 1 was characterized by transmission electron microscopy (TEM). Figure 2 As shown, Figure 2 (a) is the TEM image of the material, (b) is the C element distribution map, (c) is the F element distribution map, (d) is the N element distribution map, and (e) is the Fe element distribution map. Figure 2 The scale bars in (b~e) are all 50 nm. Figure 2 The results show that after the fluorine doping carbonization reaction, the morphology of the material still maintains a regular dodecahedron shape. The material element distribution image shows that the C, N, F, and Fe elements in the material are evenly distributed on the material, and the uniform distribution of the F element indicates that the fluorine element is successfully doped in the structure of the Fe-NC composite material.

[0074] 3) X-ray photoelectron spectroscopy (XPS) and inductively coupled plasma-optical emission spectroscopy (ICP-OES) were used to characterize the elemental composition information on the surface and bulk of the material. The results are shown in Table 1.

[0075] Table 1 Elemental composition of material surface

[0076]

[0077] a Determined by XPS

[0078] b Determined by ICP-OES

[0079] It can be seen from Table 1 that after fluorine doping, the N content on the surface of the material remains basically unchanged. The F content on the surface of Fe(0.125)@FNC was measured to be 1.19at%.

[0080] Figure 3 XPS spectra of the N1s region of Fe(0.125)@NC and Fe(0.125)@FNC materials prepared in Example 1, where (a) is Fe(0.125)@NC and (b) is Fe(0.125)@FNC; Figure 4 The XPS spectra of the C1s region of Fe(0.125)@NC and Fe(0.125)@FNC materials prepared in Example 1, where (a) is Fe(0.125)@NC and (b) is Fe(0.125)@FNC; Figures 3-4 It can be seen that after F doping, the ratios of pyridinic N, N-Fe, pyrrolic N, graphitic N and oxidized N in the material remain basically unchanged; a CF bond appears at 292.3 eV, proving that the F element is successfully introduced into the carbon matrix during the carbonization process.

[0081] 4) The surface charge density of the material in solutions with different pH values ​​was measured and analyzed using a Zeta potentiometer. The pH value corresponding to the Zeta potential of 0 is the isoelectric point (IEP) of the material. The results are shown in Table 1. Due to the high nitrogen content (9.22 at%) on the surface of the Fe(0.125)@NC material, it exhibits a high IEP value, indicating that it has a certain ability to adsorb anions in aqueous solution. Compared with the Fe(0.125)@NC material, the isoelectric point of the Fe(0.125)@FNC is improved, which is presumably caused by the doping of the highly electronegative F element into the carbon matrix.

[0082] 5) The water contact angles of different materials were tested using an optical static contact angle meter. The results are shown in Table 1. The results show that all materials exhibit excellent hydrophilicity due to the rich N-containing functional groups on the surface of the materials, while the hydrophilicity of the materials slightly decreases after fluorine doping.

[0083] Application Example 1

[0084] The Fe-NC material (Fe(0.125)@NC) and the fluorine-doped Fe-NC composite material (Fe(0.125)@FNC) prepared in Example 1 were applied to the reaction of reducing bromate ions in an aqueous phase.

[0085] A potassium bromate aqueous solution was prepared with an initial concentration of 0.08 mmol / L and an initial pH of 6.0; the reaction conditions were normal temperature and pressure; the concentration of the material in the potassium bromate aqueous solution was 0.25 g / L; the reaction time was 2 h; and the stirring rate was 400 rpm. In order to evaluate the leaching of iron ions in the process of reducing and removing bromate ions from the reducing material, the reaction solution after 2 h was taken and filtered, and the concentration of Fe ions in the solution was determined by o-phenanthroline spectrophotometry.

[0086] Figure 5 (a) shows the effect of different materials on BrO3 - The reduction rate changes with the reaction time. Figure 5 (b) shows the reduction activity of different materials during the reaction: - The reduction curve can be fitted using pseudo first-order reaction kinetics (R 2 >0.95, and the observed pseudo-first-order rate constants (k obs ,min –1 ) using the mass concentration of active sites and the initial BrO3 - The apparent constant k obs Normalized to obtain the intrinsic pseudo-first-order rate constants, k int ,mmol h –1 g Fe –1 ) to evaluate the reduction activity of the material. Figure 5 As shown in (b), after fluorine doping, the reduction activity of the material increased by 2.35 times. This may be due to the increase in the isoelectric point of the material surface (as shown in Table 1). Because the higher the isoelectric point of the material surface, the easier it is for the material to produce surface protonation in aqueous solution, which makes the material surface more likely to attract anions in aqueous solution. Solid-liquid heterogeneous reactions mainly occur on the surface of the material, so the adsorption of bromate ions on the surface of the material is a key step in the reaction, and the activity of the material is affected by the adsorption of bromate ions on the surface of the material.

[0087] In addition, the stability of the material during the reaction was evaluated by the Fe leaching level in the solution after the reaction. After the reaction, the Fe leaching concentration of Fe(0.125)@NC in the reaction solution was determined to be 55.69μg / L, while no Fe leaching was detected in the solution of Fe(0.125)@FNC material, indicating that the stability of the material was greatly enhanced after fluorine doping.

[0088] Application Example 2

[0089] The initial pH of the potassium bromate aqueous solution in Application Example 1 was adjusted to 4.0, 6.0, 8.0, and 10.0, respectively. The Fe-NC material (Fe(0.125)@NC) and the fluorine-doped Fe-NC composite material (Fe(0.125)@FNC) in Example 1 were applied to the reduction reaction to explore the effect of different reaction pH values ​​on the reduction and removal of bromate by the material. The results are as follows: Figure 6 As shown, (a) is Fe(0.125)@NC and (b) is Fe(0.125)@FNC. Figure 6 As shown in Figure 2, the reduction effect of the material on bromate ions decreases with the increase of pH in the reaction system. This pH dependence may be due to the fact that H + Directly involved in the reduction reaction and the change of the reduction potential of bromate ions with pH. When the pH value of the reaction solution increases, the surface of Fe(0.125)@NC and Fe(0.125)@FNC gradually changes from a positive to a negative state. Therefore, as the pH value increases, the electrostatic adsorption effect between the material surface and the negatively charged bromate ions decreases, resulting in a decrease in the reduction effect of the material at higher pH values. When the pH value increases from 4.0 to 10.0, the reduction effect of Fe(0.125)@NC on bromate ions decreases from 100% to 84%, while the reduction effect of Fe(0.125)@FNC can be maintained at 100% to 90%.

[0090] In addition, the experimental process calculation found that the leaching level of Fe(0.125)@NC during the reaction process was 71.21-23.73 μg / L. After fluorine doping, no Fe ion leaching was found in Fe(0.125)@FNC under the conditions of pH = 4.0-10.0, indicating that the material has excellent stability.

[0091] Application Example 3

[0092] The method in Application Example 1 was used to detect the reduction and removal effect of the Fe(0.125)@FNC material prepared in Example 1 on bromate ions.

[0093] The used Fe(0.125)@FNC material (named as Fe(0.125)@FNC') was used to repeat the testing steps;

[0094] Then, Fe(0.125)@FNC' is regenerated by fluorine doping, and the resulting material is Fe(0.125)@FNC-y, where y represents the number of times the material is regenerated by fluorine doping. The regeneration method is as follows:

[0095] (1) Collect used materials:

[0096] After the reaction, the used material was washed with ultrapure water several times and collected by filtration. The collected material was then placed in a vacuum oven and dried at 60° C. for 12 h to obtain Fe(0.125)@FNC' material.

[0097] (2) Regeneration and restoration of used materials:

[0098] Fe(0.125)@FNC' was mixed with 1000 mL of 100 mg / L perfluorooctanoic acid solution, where the mass concentration of Fe(0.125)@FNC' in the perfluorooctanoic acid solution was 1.0 g / L. The mixing time was 16 h, and the material was filtered and separated. After the material was dried in a vacuum oven at 80 °C, it was placed in the middle of the constant temperature zone of a tube furnace and heated at 25 mL min -1 In the atmosphere of high-purity nitrogen, the heating rate was 5 °C min -1 The tube furnace was heated to 700°C and maintained for 2 hours to perform fluorine doping and carbonization treatment on the material to obtain the material Fe(0.125)@FNC-1. This process was recorded as cycle-1, and the pollutant reduction test was performed again. The above regeneration-test steps were repeated to obtain the test results of cycle-2, cycle-3, cycle-4, and cycle-5.

[0099] The reacted Fe(0.125)@FNC' and the fluorine-doped regenerated material Fe(0.125)@FNC-1 were applied to the reduction reaction. The test results are as follows Figure 5 and Figure 7 As shown; the XPS characterization results are shown in Table 1. From Table 1, Figure 5 and Figure 7 It can be seen that the reduction activity of Fe(0.125)@FNC' is poor, and only 43% of the bromate ion reduction effect can be achieved within a reaction time of 2h. Compared with the Fe(0.125)@FNC material, the O element content in the Fe(0.125)@FNC' material increases, which is speculated to be caused by the oxidation of the material during the reduction reaction. After fluorine doping regeneration, the O element content on the surface of the Fe(0.125)@FNC-1 material has been significantly reduced. In particular, the surface Fe element content in the fluorine-doped carbonized material Fe(0.125)@FNC-1 is basically consistent with that of the material before regeneration. It is speculated that the perfluorinated compound acts as a self-sacrificial carbon source during the carbonization regeneration process, protecting the stability of the material structure. After 5 consecutive fluorine-doped carbonization regeneration-reuse cycles, the Fe(0.125)@FNC-5 material showed a bromate ion removal rate of nearly 100% within 60 minutes.

[0100] The above results show that the fluorine-doped carbonization regeneration method can effectively restore the activity of deactivated Fe-NC materials and is an environmentally friendly strategy for regenerating Fe-NC materials.

[0101] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a fluorine-doped Fe-NC composite material, characterized in that: The following steps are involved: The iron precursor, zinc salt, organic ligand and organic solvent are mixed and polymerized to obtain Fe@ZIF-8; Carrying out a first carbonization of the Fe@ZIF-8 to obtain a Fe-NC material; The Fe-NC material is mixed with a fluorine source solution and subjected to a second carbonization to obtain a fluorine-doped Fe-NC composite material.

2. The preparation method according to claim 1, characterized in that: The iron precursor includes one or more of ferric acetylacetonate, ferrous acetylacetonate, ferrocene and ferrophthalocyanine; the zinc salt includes one or more of zinc nitrate, zinc chloride and zinc sulfate; the organic ligand includes 2-methylimidazole; and the organic solvent includes methanol.

3. The preparation method according to claim 2, characterized in that: The molar ratio of the iron element in the iron precursor, the zinc element in the zinc salt and the organic ligand is 0.01-1.5:1:2-16.

4. The preparation method according to claim 3, characterized in that: The polymerization reaction temperature is 20-160° C. and the reaction time is 4-36 hours.

5. The preparation method according to claim 1 or 4, characterized in that: The temperature of the first carbonization is 850-1050° C., and the time is 1-4 hours.

6. The preparation method according to claim 1, characterized in that: The fluorine source in the fluorine source solution includes one or more of perfluorooctanoic acid, perfluorononanoic acid, perfluorodecanoic acid and perfluoroundecanoic acid; the concentration of the fluorine source solution is 5 to 100 mg / L; the concentration of the Fe-NC material in the fluorine source solution is 0.2 to 2 g / L.

7. The preparation method according to claim 1 or 6, characterized in that: The temperature of the second carbonization is 600-800° C., and the time is 1-4 hours.

8. The fluorine-doped Fe-NC composite material prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the fluorine-doped Fe-NC composite material according to claim 8 in reducing oxygen-containing salt pollutants in water.

10. The method for regenerating the fluorine-doped Fe-NC composite material according to claim 8, characterized in that: The following steps are involved: The fluorine-doped Fe-NC composite material after the pollutant reduction treatment in water is mixed with a fluorine compound to carry out a fluorination regeneration reaction.

Citation Information

Patent Citations

  • F-N-C composite material and preparation method and application thereof

    CN110085822A

  • Fe-N-C carbon-based oxygen reduction catalytic material as well as preparation method and application thereof

    CN111617793A

  • Metal-fluorine doped carbon composite material as well as preparation method and application thereof in electrocatalytic nitrogen fixation

    CN111686766A

  • Nitrogen-doped carbon-coated aluminum material as well as preparation method and application thereof

    CN114669741A

  • Preparation method and application of alpha or gamma-Fe modified Fe-N-C material

    CN116651483A

Cited By

  • Preparation method of axial chlorine-coordinated cobalt-based photocatalyst and application thereof in degradation of pet microplastics

    CN122644134A